Proceedings of the Sixth ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming 1997
DOI: 10.1145/263764.263769
|View full text |Cite
|
Sign up to set email alerts
|

High performance Fortran for highly irregular problems

Abstract: We present a general data parallel formulation for highly irregular problems in High Performance Fortran (HPF). Our formulation consists of (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Researchers have demonstrated that the performance of irregular parallel code can be improved by applying a combination of computation and data layout transformations. Some researches focus on providing primitives and libraries for runtime support [2,12,3,9], some provide language support such as add irregular facilities to HPF or Fortran 90 [16,11,18], and some works attempt to utilize caches and locality efficiently [4].…”
Section: Fig 1 a Typical Irregular Loopmentioning
confidence: 99%
“…Researchers have demonstrated that the performance of irregular parallel code can be improved by applying a combination of computation and data layout transformations. Some researches focus on providing primitives and libraries for runtime support [2,12,3,9], some provide language support such as add irregular facilities to HPF or Fortran 90 [16,11,18], and some works attempt to utilize caches and locality efficiently [4].…”
Section: Fig 1 a Typical Irregular Loopmentioning
confidence: 99%
“…Space-filling curves also use geometric coordinate information to attempt to ensure proximity in memory. Data are laid out in memory according to space-filling curves (e.g., Hilbert, Morton), which are continuous, non-smooth curves that pass through every point in a finite k-dimensional space [24,38,46]. Figure 2 shows an example of using the Hilbert space-filling curve.…”
Section: Recursive Coordinate Bisection (Rcb)mentioning
confidence: 99%